THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (E-WOM) PROMOTION OF STUDENT INTEREST IN BUYING SHARES: STUDY ON PNJ INVESMENT GALLERIES - Tetty Rimenda; Sabar Warsini; Elly Mirati (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2019)
ABSTRACT   The background of this research is lack students interest on buying shares.  It arise the ideato do this study.  Research begins with exploratory research to find out what promotion methods aremost preferred to arouse their interest among viral marketing, referral marketing, and communitymarketing or buzz marketing.  The unit analysis is 200 students who have a stock account at PNJinvestment gallery.  Statistic tool used in the study was multiple linear regression.  The result showsthat referral marketing, community marketing and buzz marketing influential promotion tools in arisestudent interest to buy shares.  Furthermore, positive students’ mindset is also an important factor toaccept the promotion message easily. Keywords: electronic word of mouth (EWOM), promotion, buying stock interest